Transformation of Set Expressions in Somerset Maugham’s Works - Tamazyan, Anna (Armenian Folia Anglistika, 2008)
Set expressions are widely used both in written and oral speech making it concise and colorful. The use of the transformed types of set expressions is more typical of speech and aims to enhance the emotional impact on the listener and hearer making the speech more impressive and powerful. The role of set expressions in fiction cannot be overestimated. S. Maugham’s preference of set expressions underlines the uniqueness of the author’s individual style. They make the images more colorful and impressive and the writer’s style easily recognizable.